Formerly Detained Adolescents’ Narratives: On the Interplay between Quality of Life and Desistance - Van Hecke, Nele (International journal of offender therapy and comparative criminology, 2023)
In recent years, a growing trend to consider strengths and protective factors in studies on desistance from crime has emerged. The present study explores three formerly detained adolescents’ narratives, aiming to tease out how Quality of Life (QoL) and desistance interact in pathways towards a “better life.” The narratives suggest that the journey towards a better life is highly individual, and may unfold via multiple pathways characterized by an ambivalent relationship between QoL and desistance. Alongside the importance of individual aspects and social support, societal barriers and opportunities play a significant role in creating new chances to re-build a life and prosocial identities. This reflects earlier findings that desistance is not an individual responsibility. It is essential to support young people to overcome societal barriers that impede participation in society and living a good life. This research adds to growing evidence of strengths-based approaches to rehabilitation, such as the Good Lives Model (GLM).